The Influence of Two Curing Protocols on the Colour Stability and Translucency of Resin Luting Agents - Riccardo Monterubbianesi; Flavia Vitiello; Vincenzo Tosco; Rim Bourgi; Angelo Putignano; Giovanna Orsini (Applied Sciences, 2022)
The colour properties of resin luting agents (RLAs) can influence the aesthetic of an indirect restoration. This in vitro study aims to evaluate the colour stability and translucency of RLAs cured using two different protocols by means of a spectrophotometer. Six RLAs were investigated: Enamel Plus Flow (MF), Enamel Plus (MH), light-cure Nexus Third Generation (NX3L), dual-cure Nexus Third Generation (NX3D), RelyX Veneer (RXL) and RelyX Ultimate (RXD). The samples were randomly divided into two groups (n = 5) according to the curing protocol used: the traditional protocol (P1), in which the samples were cured for 40 s, and the step luting protocol (P2), in which samples were cured for 5 s. Then, after 20 s, they were cured again for an additional 40 s. Colour changes and differences in translucency were calculated before (t0) and 1 day (t1) and 7 days (t7) after immersion of the samples in distilled water. Data were analysed using one-way ANOVA, Tukey’s test for multiple comparisons and a t-test for paired comparisons (α = 0.05). The colour and translucency of the RLAs changed between t0 and t7 (p < 0.05). In particular, only RXD showed a visually perceptible difference in colour and translucency between P1 and P2 (p = 0.00). The results of this study suggest that, except for RXD, the curing protocol does not affect the colour or translucency of the tested RLAs, even if all these materials underwent perceptible changes in colour and translucency.